Transfusion rates with intravenous tranexamic acid in total hip arthroplasty performed using the direct anterior approach. Issue 5 (September 2019) - Free, Matthew D; Owen, David H; Pascoe, Edward; Allen, Penny; Yang, Luke; Harvie, Paul
Introduction: Tranexamic acid (TXA) has been shown to reduce blood loss and transfusion requirements in patients undergoing total hip arthroplasty (THA). Most studies have focused on TXA in THA performed using a posterior approach (PA) or lateral approach. The aim of this study was to analyse the efficacy of TXA in patients undergoing THA using the direct anterior approach (DAA). Patients and methods: Using our institutional database, a retrospective analysis was conducted on consecutive primary THA performed for osteoarthritis to determine transfusion rates in patients undergoing THA with the DAA with and without TXA. Results: 146 consecutive THA were performed using DAA: 83 (56.8%) patients had TXA and 63 (43.2%) did not have TXA. Among patients who had TXA, 1 patient required a blood transfusion compared to 7 patients among those who did not have TXA (1.2% vs. 11.12%, p = 0.02). The relative risk of 0.11 (95% confidence interval 0.01–0.86) indicates an 89% reduction in the risk of requiring blood transfusion with TXA administration compared to no TXA. Conclusion: TXA is effective in reducing blood transfusion requirements for patients undergoing DAA THA.